Faktor-Faktor yang Mempengaruhi Keberhasilan Pengobatan pada Pasien Tuberkulosis Paru dengan Resistensi Obat Tuberkulosis di RS Royal Prima Jambi - Frisca Gemmi Deseva (Universitas Adiwangsa Jambi, 2024)
Background: Drug-resistant pulmonary tuberculosis (DR-TB) remains a significant challenge in global and national TB control efforts. The success of DR-TB treatment is influenced by various factors, including clinical, demographic, and behavioral components. This study aims to evaluate the factors associated with treatment success among DR-TB patients at Royal Prima Hospital Jambi. Methods: A retrospective, quantitative study design was employed. Data were collected from medical records of DR-TB patients treated between 2020 and 2024. Variables analyzed included age, sex, nutritional status, treatment adherence, and comorbidities. Multivariate logistic regression was used to identify significant predictors of treatment success. Results: Among 132 DR-TB patients, the treatment success rate was 68.9%. Significant predictors of treatment success included treatment adherence (p<0.01), good nutritional status (p=0.03), and absence of comorbidities (p=0.04). Age and sex were not statistically associated with treatment outcomes. Conclusion: Treatment success in DR-TB is significantly influenced by patient adherence, nutritional status, and the absence of comorbid conditions. Targeted interventions focusing on patient education, nutritional monitoring, and management of comorbidities are essential to improve DR-TB treatment outcomes in healthcare settings.